Formas plurais de governança das transações de suprimento de cana-de-açúcar : estudo de casos polares em quatro unidades da agroindústria canavieira paulista - Cano, Antonio (Universidade Federal de São Carlos, 2016)
The main goal of this thesis is to investigate which factors lead the agents that define the governance structures of the transactions of sugarcane supply opt for the plural of governance arrangements in producing units of the sugarcane agroindustry of the São Paulo state. The study of plural forms is the subject of several studies, conducted by researchers from the field of Organizational Economics, from the perspective of various theoretical currents, without, however, a consolidated and comprehensive framework that explains the reason for his emergency. The theoretical clipping used is of the New Institutional Economics and the Discriminant Efficient Alignment hypothesis, developed by Williamson (1985; 1991), for who economic agent, bounded by limited rationality and by other environment variables, given transaction attributes, searches to choose the most efficient structure, that minimize the costs of governance. Under such perspective, the simultaneous employment of more than one structure to govern the identical transactions would result in a sub-optimal choice, not justifying. In the sugarcane agroindustry, are used different arrangements to govern the transactions of supply of sugar cane, from those based on hierarchy in which result in some level of vertical integration, even those based on spot negotiations, contracts, contractual arrangements, or hybrid. The literature indicates the simultaneous employment of more than one structure, making the sector a promising object of study of plural forms. The research is defined as basic, exploratory and qualitative approach; the technical procedure chosen was the study of polar cases being applied four interviews with pre-defined script for its realization. In order to identify conflicting situations and increase the explanatory power of the study, were selected three polarity criteria: installed capacity; regional dynamics and type of organization. The methodological procedures are described in the specific section, right after the introduction. Later, in Chapter 1, is made a theoretical review on the chance of discriminating and efficient alignment on the plural forms. The second chapter deals with the evolution of the institutional and economic environment in the industry, as well as governance mechanisms used. Finally, the third chapter describes the cases studied and contains an analysis of the information collected. The results indicate that the use of the plural governance arrangements of the sugarcane supply transactions is predominant in the sugarcane agroindustry of São Paulo and it is a stable strategy, without perspective that is overridden by the use of natural forms. In the decision-making process on the governance structures, the agents do not measure the transaction costs of each alternative and even regard them as consciously, being, however, considered to be the attributes of the transaction, notably the high specificity of the assets, which exists on the dimensions, physical and temporal locational. There are several grounds identified in the units used for the use of plural arrangements, with emphasis on the existence of path dependence in relation to past governance decisions; need for adaptation to the borrowers ' profile of the existing governance in a certain territory; synergistic gains resulting from the combination of structures and; limitation of the firm's resources. The limitation of resources assumes a decisive role if considered that the agents present preference for fully verticalized structures, but are prevented from exercising it fully in the light of the limited resources available. The end was proposed a model adapted from the efficient alignment discriminant, which intends to add to the existing explanations for the emergence of plural forms.
Keywords: Estrutura de governança; Formas plurais; Agroindústria canavieira; Alinhamento eficiente discriminante; Suprimento de cana-de-açúcar; Governance structure; Plural forms; Sugarcane agribusiness; Discriminant efficient alignment; Sugarcane Supplying; ENGENHARIAS::ENGENHARIA DE PRODUCAO